2008
DOI: 10.1086/589298
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Candidemia: Evidence of Clusters of Smoldering Nosocomial Infections

Abstract: Background. Invasive fungal infections pose a serious threat to hospitalized patients worldwide. In particular, the prevalence of clusters of nosocomial infection among patients with candidemia remains unknown. The aim of this study was to investigate the molecular epidemiology of candidemia in a nationwide setting in Iceland during a 16-year period.Methods. The genotypes of all available fungal bloodstream isolates during 1991-2006 ( ) were detern p 219 mined by polymerase chain reaction fingerprinting with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 35 publications
(43 reference statements)
5
63
1
3
Order By: Relevance
“…The identification in this study of genetically related isolates, persistently isolated from BSI occurring in different patients in the same hospital, sometimes over several years, further reinforces the environmental acquisition of these infections. The temporal persistence of single C. parapsilosis strains over long periods of time in the same hospital or ward has been described in other studies, and was also associated with outbreaks (Á smundsdó ttir et al, 2008;Romeo et al, 2013;Viviani et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…The identification in this study of genetically related isolates, persistently isolated from BSI occurring in different patients in the same hospital, sometimes over several years, further reinforces the environmental acquisition of these infections. The temporal persistence of single C. parapsilosis strains over long periods of time in the same hospital or ward has been described in other studies, and was also associated with outbreaks (Á smundsdó ttir et al, 2008;Romeo et al, 2013;Viviani et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…This is also two to three times higher than that reported from the other Northern European countries (6.9 to 11.3 cases/100,000 population) (10,11,13) but lower than the rates reported from Spain (38.8/100,000 population) (7) and among white neonates in two population-based U.S. studies (37 and 41/100,000 population) (6,33). By genotyping of Candida blood isolates, we have previously shown that nosocomial clustering of candidemia is particularly prevalent in the neonatal intensive care unit setting (21). Our study, therefore, confirms and emphasizes the risk of candidemia in this vulnerable population and the importance of preventive measures.…”
Section: Discussionmentioning
confidence: 74%
“…Species identification was based on colony morphology following culture on chromogenic agar (CHROMagar Co., Paris, France) and analysis of sugar assimilation profiles (API 20C AUX and API ID 32C; bioMérieux). In cases where a definite species identification could not be made by these methods, species identification was achieved by using PCR fingerprinting or ITS sequence analysis, as previously described (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…The crude 30-day mortality was 30 to 40% in most population-based studies enrolling patients until the turn of the millennium (2,4,12,14,16,29,41,42,49,52) but was lower in recent studies (16,17,36) and higher for ICU patients (7,33), patients infected with C. glabrata (54), and patients with delayed initiation of appropriate antifungal treatment (20,34). Because timing and diagnostic sensitivity are still major issues in the management of fungemia, an understanding of diagnostic features, risk groups, and epidemiology is of utmost importance for selection of patients who may benefit from early antifungal treatment and for selection of the most appropriate antifungal agent before species identification is available.…”
Section: Surveillance Of Fungemia Was Initiated In Denmark In 2003mentioning
confidence: 99%